Existence of Solutions for Fractional Differential Inclusions with Antiperiodic Boundary Conditions. (4th May 2009) - Ahmad, Bashir; Otero-Espinar, Victoria
Abstract : We study the existence of solutions for a class of fractional differential inclusions with anti-periodic boundary conditions. The main result of the paper is based on Bohnenblust- Karlins fixed point theorem. Some applications of the main result are also discussed.